Trends in the development of land legislation in the Republic of Belarus: a new stage - Shakhray, Irina S.; Shingel, Natalia A. (Journal of the Belarusian State University. Law, 2023)
The innovations that have appeared in the legal regulation of land relations in connection with the adoption of a new edition of the Code of the Republic of Belarus on Land, and the prospects for further development of land legislation are analysed. The continuity of the main provisions characterising the legal regime of lands and land plots is noted. Trends in updating the land legislation of the Republic of Belarus are determined in connection with the expansion of rights to land plots of certain categories of land users and a change in the procedure for the withdrawal and provision of land plots. Proposals aimed at improving the legal regulation in the area under study are formulated.
Keywords: land reform; land legislation; land relations; land legal regime